Molecular Characterization of the Chalcone Isomerase Gene Family in Deschampsia Antarctica - Zuniga-Navarro, G (2013)
Deschampsia antarctica (Poaceae) is one of the two vascular plants known to have colonized the Antarctic region. Studies examining the biosynthesis of flavonoids, compounds which plants use, for example, for protection against overexposure to UV light or as antioxidants that scavenge free radicals and other oxidative species, in D. antarctica may provide clues to its success in that extreme environment. We characterized the family of genes encoding chalcone isomerase (CHI EC 5.5.1.6), an important enzyme involved in flavonoid biosynthesis, in D. antarctica. Sequence analysis of the three family members revealed differences in numbers of introns and lengths of coding regions among the three and suggest that DaCHI3 is likely a pseudogene (?DaChi2). Salinity stress resulted in differential mRNA expression of the DaCHI genes with ?DaCHI2 exhibiting the earliest response (3-h post-treatment), induced by as much as sevenfold, while DaCHI1 and DaCHI2 mRNAs accumulated later (3d and 5d post-treatment, respectively) and, in the case of DaCHI2, with a response of nearly sixfold. We discuss how differences in the proposed gene structures, deduced protein characteristics, and mRNA expression patterns suggest that the members of this gene family may have unique functions in the phenylpropanoid pathway in D. antarctica. © 2013 Springer-Verlag Berlin Heidelberg.